2009
DOI: 10.1089/rej.2008.0803
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Neutrophil Gelatinase-Associated Lipocalin Levels Predict Mortality in Elderly Patients with Chronic Heart Failure

Abstract: Chronic congestive heart failure (CHF) is associated with an increase in cytokines and inflammatory markers, particularly in elderly patients in whom chronic inflammation is generally present per se. In the present pilot study, neutrophil gelatinase-associated lipocalin (NGAL), a recently discovered cytokine, was analyzed together with different clinical and laboratory parameters in a small cohort of 46 elderly patients with CHF of various degrees. NGAL levels in the cohort were found to be significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 29 publications
4
68
2
3
Order By: Relevance
“…This is to some extent supported by other studies reporting that plasma NGAL predicts mortality in patients with pre-existing acute cerebral ischemia [18] or chronic heart failure [19,20], although u-NGAL was not evaluated in these studies. The more distinct associations in individuals with pre-existing cardiovascular diseases could also indicate that u-NGAL is an indicator of faster progression of atherosclerosis and chronic heart failure resulting in an increased mortality risk of cardiovascular causes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This is to some extent supported by other studies reporting that plasma NGAL predicts mortality in patients with pre-existing acute cerebral ischemia [18] or chronic heart failure [19,20], although u-NGAL was not evaluated in these studies. The more distinct associations in individuals with pre-existing cardiovascular diseases could also indicate that u-NGAL is an indicator of faster progression of atherosclerosis and chronic heart failure resulting in an increased mortality risk of cardiovascular causes.…”
Section: Discussionmentioning
confidence: 57%
“…Increased concentrations of s-NGAL and u-NGAL are found in patients with chronic heart failure [14,15] and with acute ischemic events [16,17] and increased plasma NGAL concentrations are also associated with a higher risk of mortality in these patient groups [18][19][20] and in the community [21]. However, the prospective association between the tubular kidney damage biomarker u-NGAL and cardiovascular death in the community is not known.…”
Section: Introductionmentioning
confidence: 99%
“…21 In a small study of 46 elderly congestive HF patients, higher levels of plasma NGAL were found in parallel with the clinical severity of congestive HF, the highest levels being reached in New York Heart Association class IV patients and associated with higher mortality. 24 Growing evidence suggests that NGAL may also be involved in cell survival, inflammation, and matrix degradation by modulating the activity of matrix metalloproteinase 9, an important mediator of vascular remodeling and plaque instability in atherosclerosis. This has been validated in in vitro animal studies.…”
Section: Neutrophil Gelatinaseassociated Lipocalinmentioning
confidence: 99%
“…25 Higher NGAL levels were also associated with NYHA functional class, acute decompensation, systolic blood pressure, ejection fraction and mortality and proposed as a marker for cardiovascular risk classification. 26,27 Urine NGAL levels in HF patients were also positively correlated with NTproBNP levels. 28 The superiority of NGAL when compared to other biomarkers is, its levels do not change with i.v.…”
Section: Discussionmentioning
confidence: 89%